1970
DOI: 10.1104/pp.45.6.675
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Glycosidases in the Cell Wall Metabolism of Suspension-cultured Acer pseudoplatanus Cells

Abstract: Several glycosidases have been isolated from suspensioncultured sycamore (Acer pseudoplatanus) cells. These include an a-galactosidase, an a-mannosidase, a f-N-acetylglucosaminidase, a ,B-glucosidase, and two ,3-galactosidases.The pH optimum of each of these enzymes was determined. Glycosidases have been reported in a variety of bacteria, fungi, animals, and higher plants. In plants, glycosidases have long been known to be present in seeds and storage material (1,2,4,8,9,15,17,(24)(25)(26)(27). Recently, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
1

Year Published

1971
1971
1995
1995

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 22 publications
(26 reference statements)
1
24
0
1
Order By: Relevance
“…leaves (3,8) where an involvement in galactolipid metabolism of organelle membranes was suggested, and it has also been reported in walls of epicotyl tissue (12) and in plant cell and tissue cultures (10,13). Our interest in the distribution of a-galactosidase in Cucurbita pepo resulted from our discovery that immature importing leaves possess an extremely active ability to hydrolyze raffimose, stachyose, and verbascose entering their tissue from the phloem and are incapable of any detectable synthesis or accumulation of these sugars.…”
mentioning
confidence: 81%
“…leaves (3,8) where an involvement in galactolipid metabolism of organelle membranes was suggested, and it has also been reported in walls of epicotyl tissue (12) and in plant cell and tissue cultures (10,13). Our interest in the distribution of a-galactosidase in Cucurbita pepo resulted from our discovery that immature importing leaves possess an extremely active ability to hydrolyze raffimose, stachyose, and verbascose entering their tissue from the phloem and are incapable of any detectable synthesis or accumulation of these sugars.…”
mentioning
confidence: 81%
“…The elicitor, as a foreign molecule, must approach its site of action in the soybean cell from outside the cell. Previous studies have shown that glycosidases bound to the walls of intact plant cells will hydrolyze exogenously added substrates (14,17).…”
Section: Monosaccharidementioning
confidence: 99%
“…This culture was also grown in modified B5 medium according to published methods (6,14). Cell suspension cultures of sycamore (Acer pseudoplatanus) were grown in modified M-6 medium with 20 g/l sucrose (19).…”
mentioning
confidence: 99%